2010
DOI: 10.2174/092986710791859397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Labelling Methods on Biodistribution and Imaging Properties of Radiolabelled Peptides for Visualisation of Molecular Therapeutic Targets

Abstract: Progress in genomics and proteomics provides clinical oncology with new anti-cancer drugs, which target selectively aberrantly expressed membrane proteins and associated signalling pathways in malignant cells. Molecular targeting also enables specific delivery of cytotoxic substances to tumours sparing healthy tissues. Improved selectivity of the treatment reduces side effects and widens the therapeutic window. However, only a part of the patients might benefit from such treatment due to inter- and intrapatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 158 publications
2
66
0
Order By: Relevance
“…This might affect on-target and off-target interactions, excretion, and intracellular retention of the radionuclide after internalization (41). In this way, changes in radiolabeling chemistry might have important effects on the imaging contrast obtained and optimal imaging time point.…”
Section: Adaptsmentioning
confidence: 99%
“…This might affect on-target and off-target interactions, excretion, and intracellular retention of the radionuclide after internalization (41). In this way, changes in radiolabeling chemistry might have important effects on the imaging contrast obtained and optimal imaging time point.…”
Section: Adaptsmentioning
confidence: 99%
“…Importantly, preclinical data demonstrated that different labeling approaches appreciably influence the biodistribution and targeting properties of Affibody molecules, and a careful optimization of the combination of nuclide and chelator or linker is required to obtain maximum imaging contrast 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Internalization of the targeting protein followed by metabolism and intracellular trapping of residualizing labels, such as radiometals, might make cellular binding of targeting proteins and peptides less dependent on their affinity (15). However, internalization of HER2-binding Affibody molecules is relatively slow, typically around 30% of bound conjugate per day, and in this case cellular retention of radioactivity results from the strong target binding (16)(17)(18).…”
mentioning
confidence: 99%